2016
DOI: 10.1016/j.avb.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The relation between self-conscious emotions and delinquency: A meta-analysis

Abstract: Self-conscious emotions are expected to be related to delinquency, as they guide moral decision making. In the current study, two separate multilevel meta-analyses were performed to examine the overall relation between guilt, shame and delinquency. In addition, possible moderating factors were examined. In total, 25 studies with 24 independent samples, reporting on 75 effect sizes, were included. The results showed significant negative associations between guilt and delinquency (r = -.278), and between shame a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 71 publications
1
25
0
3
Order By: Relevance
“…The theory of reintegrative shaming argues that shame is important to crime control and to problem solving (Leach and Cidam 2015;Spruit et al 2016). Societies in which rape is not shameful will have a lot of rape.…”
Section: Conversations Across the Curriculum Of Crimesmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of reintegrative shaming argues that shame is important to crime control and to problem solving (Leach and Cidam 2015;Spruit et al 2016). Societies in which rape is not shameful will have a lot of rape.…”
Section: Conversations Across the Curriculum Of Crimesmentioning
confidence: 99%
“…The preceding section was partly about the general deterrence that arises from citizens talking with one another about why something like rape or torture is wrong. Reintegrative shaming theory advances the idea that general deterrence by means of the internalization of shame (anticipated self-shaming rather than shame sanctions) combined with a path out of shame (Leach and Cidam 2015;Spruit et al 2016) is more important than deterrence by sentences handed down by courts (Ahmed et al 2001). It is also about the restorative justice political strategy for community support for a less punitive justice system.…”
Section: Minimal Sufficiency Of General Deterrencementioning
confidence: 99%
“…Shame and guilt have 'presumed roles in inhibiting immoral, socially undesirable behaviour and in fostering altruistic, prosocial behaviour' (Tangney, Stuewig, & Hastings, 2011, p. 1). A meta-analysis of 25 studies showed significant negative associations between guilt and delinquency (r =-.278) and between shame and delinquency (r =-.130) regardless of the type of shame and guilt measure or the type of crime (Spruit, Schalkwijk, van Vugt, & Stams, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Proses mengevaluasi keputusan berdasarkan standar moral tersebut memunculkan emosi, yang disebut sebagai emosi moral (Tangney, Stuewig, & Mashek, 2007). Ketika seseorang mengevaluasi bahwa tindakannya bertentangan dengan standar moral, maka emosi moral akan muncul dalam bentuk negatif (Spruit et al, 2016). Dua bentuk emosi moral yang negatif tersebut adalah (1) emosi malu, dan (2) emosi bersalah.…”
unclassified
“…Meskipun disebut sebagai emosi moral negatif, tetapi kedua emosi moral tersebut dibutuhkan oleh remaja. Hal ini dikarenakan emosi moral mengarahkan seseorang untuk mengambil keputusan yang berkaitan dengan moral (Eisenberg & Pizarro dalam Spruit et al, 2016). Remaja yang sudah mencapai tahap perkembangan moral konvensional, menjadikan standar sosial sebagai acuan standar moralnya.…”
unclassified